Acute pulmonary embolism following radiofrequency catheter ablation in a young asian female on hormonal contraceptive injection - Triatmojo, Nicodemus; Rizal, Ardian; Wikananda, Adhika Prastya; Kurnianingsih, Novi; Anjarwani, Setyasih (Universitas Brawijaya, 2026)
Background: Acute pulmonary embolism (APE) is an uncommon yet severe complication following radiofrequency catheter ablation (RFCA) for arrhythmic disorders, with reported incidences ranging from 0% to 1.7%. Hormonal contraceptive injections, specifically Depot Medroxyprogesterone Acetate, significantly increase the risk of venous thrombosis. Early identification of APE is challenging due to non-specific symptoms, but critical indicators include sudden shortness of breath, chest pain, and loss of consciousness. Timely and tailored treatment, including weight-based dose adjustments for fibrinolytic therapy in Asian patients, is crucial for optimal outcomes. Case Presentation: We present the case of a 23-year-old Asian female with no prior history of thromboembolic diseases, who was on Depot Medroxyprogesterone Acetate for contraception. She underwent an uncomplicated RFCA procedure for frequent premature ventricular contractions. Patient was immobilized for nine hours post-procedure, upon her first attempt to mobilize and walk to the bathroom, she suddenly experienced shortness of breath, chest pain, and a brief loss of consciousness. Her vital signs were unstable, with a blood pressure of 85/55 mmHg, heart rate of 133 bpm, respiratory rate of 32 breaths/minute, and oxygen saturation of 88%. Echocardiography revealed right ventricular dilatation and a positive McConnell sign. A CT pulmonary angiography confirmed a filling defect in the left pulmonary artery, leading to an APE diagnosis. Considering her Asian ethnicity and low BMI, the patient was successfully treated with a reduced dose of alteplase (50 mg) administered over two hours to minimize bleeding risk. Her vital signs stabilized during fibrinolytic therapy, with no hemorrhagic complications. Following three months of oral rivaroxaban treatment, a follow-up CT pulmonary angiography revealed complete resolution of the embolism. Conclusions: This case underscores that APE, though rare, is a serious complication of RFCA, especially when combined with prolonged immobilization and hormonal contraceptive use. The abrupt onset of symptoms, including shortness of breath and loss of consciousness upon initial mobilization, is a critical indicator of Acute PE. Early mobilization within 2-4 hours post-RFCA is indicated to minimize embolic risk. Individualized treatment strategies, such as weight-based fibrinolytic dosing, are essential for managing APE in specific patient populations to optimize efficacy and safety. Clinicians should exercise caution with patients using hormonal contraception undergoing procedures involving vascular puncture.